ON EFFECTIVENESS OF NEW FORM OF FUSAFUNGINE - G.L. Balyasinskaya ("Paediatrician" Publishers LLC, 2010)
Author discusses advantages of topical antibacterial treatment of inflammatory diseases of upper airways. Advantages of new form of Bioparox (fusafungine) are rapid effect from the 1st day of treatment, optimized dosing regimen, additional children's attachment for nose and increased adherence to therapy. Key words: sinusitis, acute respiratory infections, pharyngitis, treatment, fusafungine. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):107-110)